Software-Defined Optical Coherence Measurement of Seawater Refractive Index Variations - Jiaxin Zhao; Xinyi Zhang; Qi Wang; Liyan Li; Songtao Fan; Yongjie Wang; Yan Zhou (Sensors)
The seawater refractive index is an important parameter in marine environments, with its variations depending on the specific environmental conditions. During practical applications, modulation parameters such as the sampling rate, bandwidth, and filters directly affect the signal-to-noise ratio (SNR) and need to be adjusted in real-time according to the characteristics of the target signal. Low-cost software-defined radio (SDR) offers significant advantages in this regard. This paper proposes an optical coherence measurement method for seawater refractive index changes based on orthogonal demodulation using SDR along with simulation calculations, and the results demonstrate that the resolution of the refractive index change rate is <semantics>3.165×10−9</semantics> RIU/s, corresponding to a refractive index change resolution of <semantics>10−10</semantics> RIU (frequency range 1 Hz–100 Hz, measurement range 0.1 m). By adopting SDR as the implementation platform for the demodulation algorithm and using a radio-frequency source to simulate interference signals for demodulating the refractive index variation, the results show that the relative error of the SDR demodulation results is below 0.3%. Additionally, this study developed a software-defined optical coherence measurement system for the seawater refractive index and measured the refractive index changes in deionized water during heating. The experimental results showed that the root mean square error (RMSE) of the refractive index changes obtained through SDR demodulation was <semantics>5.68×10−6</semantics> RIU. This research provides a novel demodulation method for high-precision measurements of seawater refractive index changes under different marine environments.